Group portrait of attendees at religious meeting in Beulah Park - Gordon, John C., 1887-1967 (photographer):::Creator::::::::::::
Group portrait of a large gathering at Beulah Park, apparently, the park no longer exists. It was probably located off the El Rancho Drive exit on Highway 17 in Santa Cruz County, California.